Penerapan Metode Fun Learning Untuk Meningkatkan Hasil Belajar Dalam Pembelajaran Tematik Sekolah Dasar - Zaeni, Abu (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The Fun Learning Method is an instructional approach that prioritizes joy and enjoyment, focusing on the psychological conditions of students and the learning environment. The goal is to create a comfortable learning atmosphere, fostering love and motivation for learning among participants. This research aims to explore the steps of implementing the Fun Learning method at MI NU As-salaam. The study adopts a qualitative research method with a descriptive approach, focusing on portraying subjects or objects of research, such as individuals, institutions, communities, and other entities. The descriptive approach is employed to investigate or solve problems by providing detailed descriptions of the characteristics or conditions of the subjects or objects. Data collection methods include interviews, observations, and documentation, allowing for a profound understanding of the researched phenomenon. The results of the study indicate that the steps of the Fun Learning method involve creating a lively learning environment through musical activities, singing, and cheers. Subsequently, the teacher presents the learning topic and provides motivation. Detailed explanations of the material, along with example problems, are given to reinforce understanding. After students grasp the material, the teacher forms groups to enhance interaction and assigns tasks using worksheets or textbooks.